2011
DOI: 10.1089/jamp.2010.0835
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Temperature of Thermally Generated Inhalation Aerosols

Abstract: Technical standards indicate that the upper limit on inhaled T(wb) for safety and tolerability is 50°C, and inhalation at that temperature can be sustained for 1 h. Peak values of T(wb) from the Staccato system are well below that threshold, approximately 30°C at nominal conditions and approximately 40°C at a combination of extreme conditions. Moreover, the peak lasts for only a few seconds, well under the time limit of 1 h. These results suggest that aerosols generated with the Staccato system will be safe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There are two inhalers on the market based on thermal condensation principles, the Staccato® system (Alexza pharmaceuticals) and Aria® system (Chrysalis technology), which A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 22 use thermal vaporization for aerosol generation 77 . The effect of temperature 77 , initial film thickness 78 and energy 79 on the condensation aerosol was previously studied.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There are two inhalers on the market based on thermal condensation principles, the Staccato® system (Alexza pharmaceuticals) and Aria® system (Chrysalis technology), which A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 22 use thermal vaporization for aerosol generation 77 . The effect of temperature 77 , initial film thickness 78 and energy 79 on the condensation aerosol was previously studied.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Size distribution of the resublimated particles is controlled by the airflow velocity over the vaporizing compound (96). Even though the device locally generates high temperatures, it was shown that the peak wet bulb temperature of the outlet stream of 39.9 ±0.1°C, determined in a worst-case scenario setup, is well below the recommended standard of 50°C (97). In vitro experiments using the NGI at a flow rate of 30 L/min showed an ED of 89-102% depending on the preoperating stress , and can be evaluated as low.…”
Section: Staccatomentioning
confidence: 99%